Control test at Hercules Hopewell plant - Hercules Incorporated (1951)
General view of laboratory operator Donald R. Stevens checking the filtration characteristics of viscose solutions produced in the Cellulose Department at the Hercules Powder Company plant located in Hopewell, Virginia. Per notations accompanying the photograph, the test depicted here was one of a series of control tests applied to so-called "chemical cotton," i.e. purified cellulose obtained from raw cotton linters, manufactured at the plant. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Laboratories; Research, Industrial; Hercules Incorporated; Corporations; Cellulose; Viscosity; Scientific apparatus and instruments